2012
DOI: 10.1155/2013/678140
|View full text |Cite
|
Sign up to set email alerts
|

Case Study of the Relationship between Aqua Regia and Real Total Contents of Harmful Trace Elements in Some European Soils

Abstract: Bothreal totalandaqua regiacontents of trace elements in soils are often denominated by the same word “total” though the results are not identical. The formulas would be helpful for recalculation ofaqua regiacontents toreal totals. Data for primary formulas were taken from the International Soil-Analytical Exchange Program of Wageningen Evaluating Programs for Analytical Laboratories. The degree of extractability DE of element in a sample was calculated by weighting the ratios of median contents inaqua regiato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 25 publications
0
13
1
Order By: Relevance
“…About 18% of the total content of As and Mo may not be extracted from soil even by aqua regia, because their median degree of extractability in aqua regia from some European soil samples analysed by ISE participants is only 82% (Taraškevičius et al 2013). About 18% of the total content of As and Mo may not be extracted from soil even by aqua regia, because their median degree of extractability in aqua regia from some European soil samples analysed by ISE participants is only 82% (Taraškevičius et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…About 18% of the total content of As and Mo may not be extracted from soil even by aqua regia, because their median degree of extractability in aqua regia from some European soil samples analysed by ISE participants is only 82% (Taraškevičius et al 2013). About 18% of the total content of As and Mo may not be extracted from soil even by aqua regia, because their median degree of extractability in aqua regia from some European soil samples analysed by ISE participants is only 82% (Taraškevičius et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Respective methods are described in Baltrūnas et al (2013c). The contents of 10 harmful chemical elements As, Ba, Cr, Cu, Mn, Mo, Ni, Pb, V, zn were compared with their maximum permitted concentrations (MPC) in soil (Taraškevičius et al 2013). Energy-dispersive x-ray fluorescence equipment SPECTRO XEPOS with TurboQuant for pressed pellets calibration method was used for Step the determination of total contents of chemical elements in 680 samples.…”
Section: Methodsmentioning
confidence: 99%
“…Past works have shown that aqua regia extraction may lead to an underestimation of the amount of metals such as Co, Cd, Cr and Ni by up to 50% [18], [19]. The reasons for this underestimation lies on the type of matrix and the strength of the solvent itself, which is unable to dissolve silicates and aluminium and iron oxides to which some metals may be bound.…”
Section: Introductionmentioning
confidence: 99%
“…:HNO 3conc. , 1:3 ratio), [22]. Next the concentrations of bioavailable (Zn Bio ) as well as reactive (Z nReac ) zinc forms were assessed by the chemical tests 0.10 mol NaNO 3 dm -3 [23] and 0.11 mol CH 3 COOH dm -3 (first fraction), according to the BCR method [24], respectively.…”
Section: Soil Chemical Analysesmentioning
confidence: 99%